2013
DOI: 10.1371/journal.pone.0072029
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cell Renewal in Adult Mice Controls the Onset of Obesity

Abstract: The hypothalamus plays a crucial role in the control of the energy balance and also retains neurogenic potential into adulthood. Recent studies have reported the severe alteration of the cell turn-over in the hypothalamus of obese animals and it has been proposed that a neurogenic deficiency in the hypothalamus could be involved in the development of obesity. To explore this possibility, we examined hypothalamic cell renewal during the homeostatic response to dietary fat in mice, i.e., at the onset of diet-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 47 publications
4
75
2
Order By: Relevance
“…Thus, due to their localization in the hypothalamus, tanycytes are in a privileged position to detect hormonal, nutritional and mitogenic signals released by peripheral organs or present in the CSF. Recent studies reveal that in response to nutritional signals, tanycytes are capable of differentiating into anorexigenic neurons (Gouaze et al, 2013; Recabal et al, 2017), which strongly supports the notion that these cells are involved in the control of feeding behavior.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, due to their localization in the hypothalamus, tanycytes are in a privileged position to detect hormonal, nutritional and mitogenic signals released by peripheral organs or present in the CSF. Recent studies reveal that in response to nutritional signals, tanycytes are capable of differentiating into anorexigenic neurons (Gouaze et al, 2013; Recabal et al, 2017), which strongly supports the notion that these cells are involved in the control of feeding behavior.…”
Section: Discussionmentioning
confidence: 77%
“…Dietary factors modulate adult hypothalamic neurogenesis. High fat diet, for example, was reported to increase proliferation and to stimulate generation of neurons expressing anorexigenic peptides Gouazé et al, 2013). It was also observed that ablation of cell genesis resulted in accelerated weight gain and obesity onset under high fat diet (Pierce and Xu, 2010;Gouazé et al, 2013).…”
Section: Systemic Factors With Links To Metabolism Modulate Adult Neumentioning
confidence: 99%
“…High fat diet, for example, was reported to increase proliferation and to stimulate generation of neurons expressing anorexigenic peptides Gouazé et al, 2013). It was also observed that ablation of cell genesis resulted in accelerated weight gain and obesity onset under high fat diet (Pierce and Xu, 2010;Gouazé et al, 2013). Thus, it is hypothesized that modulation of adult neurogenesis in accordance to the nutritional status serves to maintain energy homeostasis through the control of food intake and bodyweight (Sousa-Ferreira et al, 2014).…”
Section: Systemic Factors With Links To Metabolism Modulate Adult Neumentioning
confidence: 99%
“…This finding suggests a degree of plasticity that is evolutionarily conserved and likely extends to humans as well (Batailler et al 2013;Dahiya et al 2011;Noguiera et al 2014). Both juvenile and adult mammalian hypothalamus exhibit ongoing neurogenesis that can be regulated by growth and differentiation factors (Pencea et al 2001;Xu et al 2005;Kokoeva et al 2005;Perez-Martin et al 2010;Robins et al 2013b), diet Li et al 2012;McNay et al 2012;Gouaze et al 2013;Bless et al 2014), antidepressants (Sachs and Caron 2014), exercise (Matsuzaki et al 2015), and hormones (Ahmed et al 2008;Bless et al 2014). Although these studies generally agree that levels of constitutive hypothalamic neurogenesis are much lower than those seen in well-characterized neurogenic zones in the adult brain, such as the subventricular zone of the lateral ventricles or the subgranular zone of the lateral hypothalamus , they often report differing effects of extrinsic factors on cell proliferation and neurogenesis in hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while multiple groups have reported that long-term administration of HFD inhibits cell proliferation and neurogenesis in hypothalamic parenchyma (Li et al 2012;McNay et al 2012;Gouaze et al 2013;Bless et al 2014), studies investigating acute responses to HFD have reported increased hypothalamic cell proliferation and neurogenesis (Thaler et al 2012;Gouaze et al 2013). Acute HFD administration has also been reported to rapidly induce hypothalamic inflammation, increasing cytokine signaling (Thaler et al 2012).…”
Section: Introductionmentioning
confidence: 99%